PENGARUH PENDEKATAN PROBLEM POSING TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Suri M Rahayu; O Liyana; Eka N Anggraini (Hipotenusa Journal of Research Mathematics Education (HJRME), 2020)
The research used is experimental research. The population in this study were all students of class X SMA Al Azhar 3 Bandar Lampung. The population is spread in 8 classes. Two classes were sampled, namely class X 3 as the experimental class and class X 1 as the control class. Sampling technique using the Cluster Rundom Samplin Technique. Data analysis used statistical formulas. The purpose of this study was to determine the effect of the problem approach on students' mathematics learning outcomes. Based on the research results obtained  and the total distribution at the significant level  is known while the significant level  is known.  Thus, it appears that both at the level  and it is  not in the area  of acceptance, so that there is "The Effect of the Application of the Problem Posing Approach on Students' Mathematics Learning Outcomes"